2021
DOI: 10.1016/j.joen.2020.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Dental Care During Italian Lockdown: A Cross-sectional Survey

Abstract: Introduction: On March 9, 2020, the Italian government imposed a nationwide lockdown to contain the spread of coronavirus disease 2019. Oral health services were limited to only essential services. Nonurgent treatments were postponed. This study described the management of urgent dental care in northern Italy during the lockdown, with a particular focus on the province of Brescia. Methods: A cross-sectional survey was administered to Italian dentists at the end of the lockdown (May 3, 2020). A total of 1407 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Oral diagnoses and dental treatments significantly reduced during lockdown and reopening, which was mainly due to the drop in endodontic emergencies and tooth extractions, which represent the most prevalent categories in all time periods, as previously reported in a comparable dental setting in both the pre-pandemic and during COVID-19 outbreak [22,26,[33][34][35][36]. More than 80% of dental care in Italy is provided by private practitioners; moreover, less than 50% of Italian citizens aged 15-65 years undergo at least one dental check-up per year according to the 2017 Italian National Institute of Statistic Report [37].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Oral diagnoses and dental treatments significantly reduced during lockdown and reopening, which was mainly due to the drop in endodontic emergencies and tooth extractions, which represent the most prevalent categories in all time periods, as previously reported in a comparable dental setting in both the pre-pandemic and during COVID-19 outbreak [22,26,[33][34][35][36]. More than 80% of dental care in Italy is provided by private practitioners; moreover, less than 50% of Italian citizens aged 15-65 years undergo at least one dental check-up per year according to the 2017 Italian National Institute of Statistic Report [37].…”
Section: Discussionsupporting
confidence: 71%
“…National and international guidelines released by the different Dental Associations have advocated limiting dental activities to emergencies and urgent life-threatening conditions in order to encourage social distancing [13,24,25]. It was reported that private dental practitioners had coped with many dental urgencies through phone triage, sending drug prescriptions via email, and conducting online consultation via smartphones, tablets, or PCs [26]. The UDCS of San Paolo Hospital did not switch to a remote model workflow for dental emergency care during the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study highlighted that return to normalcy has a different meaning after one year of the COVID-19 outbreak. Job insecurity and fear of COVID-19 continue to characterize the daily dental activity similar to the first days of the COVID-19 pandemic [14]. Therefore, the new normalcy results from the balance between the management of any depressive symptoms associated with uncertainty and fear [54] and the need to find solutions and compromises to adapt to the new scenario [5].…”
Section: Discussionmentioning
confidence: 99%
“…Urgent dental treatments were handled, taking all recommended precautions to prevent COVID-19 infection, while non-urgent dental treatments were managed by telephone and, when possible, deferred. Nevertheless, an increasing sense of uncertainty and concern about the effective restarting of dental activity remained after lockdown [14]. A recent survey demonstrated that 57.2% of the dentists were not trained sufficiently to restart after lockdown [15].…”
Section: Introductionmentioning
confidence: 99%
“…Dental clinics and institutions reported changes in the presentation and management of endodontic/dental emergencies during the initial outbreak of COVID-19. There were changes in policies at these institutions that limited their patient flow to those with true emergencies (e.g., severe pain and/or swelling; life threatening infections) that could not be managed remotely ( 3 , 4 , 5 , 6 ). Centreville Endodontics and Capitol Endodontics, two private offices in Washington DC and Northern Virginia area, that are about 25 miles apart and serve similar population of patients and are operated by one team of endodontists, stayed fully operational during the period of March 16 to May 31, 2020.…”
Section: Introductionmentioning
confidence: 99%